The Mediator Kinase Module Restrains Epidermal Growth Factor Receptor Signaling and Represses Vulval Cell Fate Specification in Caenorhabditis elegans. Issue 2 (29th December 2015) - Grants, Jennifer M; Ying, Lisa T L; Yoda, Akinori; You, Charlotte C; Okano, Hideyuki; Sawa, Hitoshi; Taubert, Stefan
Abstract: Cell signaling pathways that control proliferation and determine cell fates are tightly regulated to prevent developmental anomalies and cancer. Transcription factors and coregulators are important effectors of signaling pathway output, as they regulate downstream gene programs. In Caenorhabditis elegans, several subunits of the Mediator transcriptional coregulator complex promote or inhibit vulva development, but pertinent mechanisms are poorly defined. Here, we show that Mediator's dissociable cyclin dependent kinase 8 (CDK8) module (CKM), consisting of cdk-8, cic-1 /Cyclin C, mdt-12 /dpy-22, and mdt-13 /let-19, is required to inhibit ectopic vulval cell fates downstream of the epidermal growth factor receptor (EGFR)-Ras-extracellular signal-regulated kinase (ERK) pathway. cdk-8 inhibits ectopic vulva formation by acting downstream of mpk-1 /ERK, cell autonomously in vulval cells, and in a kinase-dependent manner. We also provide evidence that the CKM acts as a corepressor for the Ets-family transcription factor LIN-1, as cdk-8 promotes transcriptional repression by LIN-1 . In addition, we find that CKM mutation alters Mediator subunit requirements in vulva development: the mdt-23 /sur-2 subunit, which is required for vulva development in wild-type worms, is dispensable for ectopic vulva formation in CKM mutants, which instead display hallmarks of unrestrained Mediator tail module activity. We propose a model whereby the CKM controls EGFR-Ras-ERK transcriptional output by corepressing LIN-1 and by fine tuning Mediator specificity, thus balancing transcriptional repression vs. activation in a critical developmental signaling pathway. Collectively, these data offer an explanation for CKM repression of EGFR signaling output and ectopic vulva formation and provide the first evidence of Mediator CKM-tail module subunit crosstalk in animals.